2003
DOI: 10.1073/pnas.1533185100
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-dependent and -independent effects of splice variant 1 of growth hormone-releasing hormone receptor

Abstract: Existing evidence indicates that, in addition to its neuroendocrine action, growth hormone-releasing hormone (GHRH) acts directly on several nonpituitary tissues, especially neoplasms, and stimulates cell proliferation. We have recently reported that a splice variant of the receptor (SV1) is expressed in various normal tissues and particularly in tumor tissues, producing mitogenic effects on GHRH binding. By using HEC-1A human endometrial carcinoma cells, which express endogenous SV1, we show that, in addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 50 publications
4
53
0
1
Order By: Relevance
“…The T47D cell line has the highest expression of SV-1 of the GHRH receptor with its ligand-dependent and independent activity. The inhibition of the gene expression for GHRH in T47D breast cancer cell line did not have the potent antiproliferative effect found in the other two breast cancer cell lines (MDA-MB-468 and MDA-MB-435S), possibly because the ligand independent activity of the SV1 continued to enhance the proliferation rate of the T47D cells (Kiaris et al, 2003;Barabutis et al, 2007).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…The T47D cell line has the highest expression of SV-1 of the GHRH receptor with its ligand-dependent and independent activity. The inhibition of the gene expression for GHRH in T47D breast cancer cell line did not have the potent antiproliferative effect found in the other two breast cancer cell lines (MDA-MB-468 and MDA-MB-435S), possibly because the ligand independent activity of the SV1 continued to enhance the proliferation rate of the T47D cells (Kiaris et al, 2003;Barabutis et al, 2007).…”
Section: Discussionmentioning
confidence: 79%
“…Some tumours also express pituitary type of GHRH receptor Christodoulou et al, 2006). Besides its ligand-dependent activity, a ligand-independent activity of SV1 has also been demonstrated (Kiaris et al, 2003). A recent study showed the stimulation and proliferation of MCF-7 breast cancer cells after the transfection of SV1 (Barabutis et al, 2007).…”
mentioning
confidence: 99%
“…nlm.nih.gov). However, previous studies showed that the immunostaining of HEC-1A human endometrial cancer cells was abolished when the expression of SV1 was ablated by SV1-antisense RNA (32). Moreover, MDA-MB-231 human breast cancer cells that do not express SVs did not show corresponding protein bands in the Western blots, whereas RL and HT lymphomas presented a predicted protein of 40 kDa, which would also correspond to SV1 (25).…”
Section: Discussionmentioning
confidence: 85%
“…This method consisted of two consecutive PCR reactions that could accomplish the amplification of cDNA for all four SVs at the sizes of 720, 566, 390, and 335 bp corresponding to SV1, SV2, SV3, and SV4, respectively (18,22,23). Even though SV1 is the only SV of GHRH-R that was proven to respond physiologically to GHRH binding (31,32), we recently established a protocol that could detect the expression of each SV separately, without using the method of nested PCR. Nonetheless, our main objective was to determine whether the mRNA and protein for the pGHRH-R could be expressed in some tumor tissues.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is supported by the demonstration by our group of the presence of GHRH-R and truncated splice variants of GHRH-R (SV-1-4) in non-malignant human tissues, various human cancer cell lines and human prostate cancer specimens (3)(4)(5)(6). Of the four truncated receptors, SV-1 has the greatest structural similarity to GHRH-R and is probably the main receptor that mediates the effects of GHRH and its antagonists in tumours (7)(8)(9). In the present study, we investigated the expression of GHRH-R, SV-1, SV-2 and SV-4 in normal and malignant human tissues of the gastrointestinal tract by means of immunohistochemistry and mRNA analyses.…”
Section: Introductionmentioning
confidence: 89%